(untitled) (Research, Society and Development, 2024)
Okra is a vegetable of great nutritional value, and its culinary versatility, as well as its adaptability to different climatic conditions, make it an interesting option for vegetable crops. However, aspects related to its development and management still require further study to allow for increases in productivity. Cultivation under different spacing can interfere with the emission of lateral branches, thus altering its production. Therefore, the objective of this study was to evaluate the influence of different row spacings on the vegetative development and production of the ’Santa Cruz 47’ okra cultivar. A randomized block design was used, with five different row spacings (0.80; 0.90; 1.00; 1.10; and 1.20 m). It was observed that higher plant density reduced the number of productive stems and, consequently, resulted in a lower number of fruits per plant. However, this higher density provided the highest productivities, suggesting the importance of proper spacing to optimize okra production. These results provide valuable insights for farmers and researchers interested in maximizing the yield of this vegetable.